Şeyhülislâm Hoca Sâdeddin Efendi’nin Fetva Mecmuası (Kerâhiye ve İstihsan örneği) - Akyüz, Elif (My University, 2019)
XVI. yy Osmanlı şeyhülislâmlarından biri olan Hoca Sâdeddin Efendi, 1536’da Kanuni Sultan Süleyman zamanında İstanbul’da dünyaya gelmiş ve saray merkezli iyi bir tahsil görmüştür. Hoca Sâdeddin Efendi’nin önemli bir ilim adamı olması ile birlikte padişah hocası olması bazı zamanlarda idarede etkili olmasına imkan sağlamıştır. Sâdeddin Efendi 1598’de Üçüncü Mehmed döneminde şeyhülislâm olmuş, 1599 yılında da vefat etmiştir.Hoca Sâdeddin Efendi’nin şeyhülislâmlığı sırasında verdiği fetvalardan oluşan Fetva Mecmuası’nın tespit edebildiğimiz tek nüshası vardır. Mecmua’da kimi zaman sonraki dönem şeyhülislâmlarına ait fetvalara yer verilmiş olması, Mecmua’nın Hoca Sâdeddin Efendi’nin vefatından sonra oluşturulduğunu göstermektedir. Bununla birlikte Mecmua’nın müstensihi bilinmemektedir.Fetva Mecmuası’nda yer alan “Kitâbü’l-kerâhiyye ve’l-istihsân” bölümünde yemin, nikah, talak, ilim, mahkeme, mali muamelat, gayr-i Müslimlerle ilişkiler gibi pek çok konu bulunmaktadır. Bölüm konularının geniş kapsamlı olması döneminin siyasi, ictimai, askeri, ekonomik vb. özelliklerine ışık tutmaktadır. Ayrıca Mecmua’nın ilgili bahsinin daha önceki asırlarda oluşturulan muteber fetva kitaplarındaki fetvalarla mukayesesi, farklı dönemlerde benzer konularda verilen fetvalardaki benzerlik ile zamanın değişmesiyle fetvadaki değişimi göstermesi açısından önem arz etmektedir.

Hodja Sadeddin Efendi, an Ottoman sheikh al-Islam of the 16th century, was born in Istanbul in 1536 during the reign of Suleiman the Magnificent and received a good education at the palace. Being an important scholar and a teacher of the sultan enabled Hodja Sadeddin Efendi to be effective in the administration from time to time. Sadeddin Efendi became sheikh al-Islam during the reign of Mehmed III in 1598 and passed away in 1599.We have found only one copy of the Fatwa Journal composed of the fatwas Hodja Sadeddin Efendi gave when he was sheikh al-Islam. The Journal sometimes included the fatwas of the sheikh al-Islam of later periods, which indicates that The Journal was created after the demise of Hodja Sadeddin Efendi. However the copyist of The Journal is not known.The Fatwa Journal's “Kitâbü'l-kerâhiyye ve'l-istihsân” section included many subjects such as oath, wedding, divorce, science, court, financial transactions, and relations with non-Muslims. The subjects included in this section are wide-ranging, which highlights the political, social, military, and economic characteristics of the period. Also, the comparison of the relevant parts of the Journal with the fatwas in the recognized fatwa books which were formed in the previous centuries is important in terms of showing the change in the fatwa with the change of time and the similarity in the fatwas given on similar subjects in different periods.
Keywords: 16. Yüzyıl al-Fatwa; al-Istihsan; al-Karahiyah; century; Fatwa Journal; Fetva; Fetva Mecmuası; Hoca Sadeddin Efendi; Hodja Sadeddin Efendi; Islam; Islamic law; İslam hukuku; İslamiyet; İstihsan; Kerâhiye; Makruh; Mekruh; Osmanlı; Ottoman; Sheikh al-Islam; Şeyhülislâm; XVI